A Review on Leading-Edge Erosion Morphology and Performance Degradation of Aero-Engine Fan and Compressor Blades - Lei Shi; Shuhan Guo; Peng Yu; Xueyang Zhang; Jie Xiong (Energies, 2023)
The leading edges of aero-engine fan and compressor blades suffer from severe erosion due to the inhalation of suspended particulates in the low-altitude atmosphere during long-term transport. A small deformation of the leading edge can significantly change the aerodynamic performance under a strong non-linear effect, leading to increased operation and maintenance costs for engines. This review first focuses on leading-edge erosion morphology during service, and models of these damages. Secondly, the performance degradation caused by eroded leading edges on different classes of engine components, including airfoils, blades, compression systems, and the whole engine, are reviewed. Finally, optimization methods for eroded blade leading edges and their effects on performance recovery are summarized. This paper contributes to an in-depth understanding of the erosion mechanism of blade leading edges in terms of status and its effect, and is a good reference for establishing erosion leading edge repair methods and improving the level of automated repair.